Relationship between intracardiac impedance and left ventricular contractility in patients undergoing cardiac resynchronization therapy - Ginks, Matthew R. (Oxford University Press, 2011)
AIMS: Cardiac resynchronization therapy (CRT) has dramatically improved the symptoms and prognosis of patients with heart failure in large randomized clinical trials. Optimization of device settings may maximize benefit on an individual basis, although the best method for this is not yet established. We evaluated the use of cardiogenic impedance measurements (derived from intracardiac impedance signals) in CRT device optimization, using invasive left ventricular (LV) dP/dt(max) as the reference. METHODS AND RESULTS: Seventeen patients underwent invasive haemodynamic assessment using a pressure wire placed in the LV cavity at the time of CRT device implantation. Intracardiac impedance measurements were made at different atrioventricular (AV) and interventricular (VV) delays and compared with LV dP/dt(max). We assessed the performance of patient-specific and generic impedance-based models in predicting acute haemodynamic response to CRT. In two patients, LV catheterization with the pressure wire was unsuccessful and in two patients LV lead delivery was unsuccessful; therefore, data were acquired for 13 out of 17 patients. Left ventricular dP/dt(max) was 919 ± 182 mmHg/s at baseline and this increased acutely (by 24%) to 1121 ± 226 mmHg/s as a result of CRT. The patient-specific impedance-based model correctly predicted the optimal haemodynamic response (to within 5% points) for AV and VV delays in 90 and 92% of patients, respectively. CONCLUSION: Cardiogenic impedance measurements are capable of correctly identifying the maximum achievable LV dP/dt(max) as measured by invasive haemodynamic assessment. This study suggests that cardiogenic impedance can potentially be used for CRT optimization and may have a role in ambulatory assessment of haemodynamics.